GROWTH AND YIELD OF CALLIANDRA (Calliandra calothyrsus) PLANTS WAS GIVEN VARIOUS DOSAGE OF VERMICOMPOST FERTILIZER - A. A., Prabowo; Roni, N. G. K.; Wirawan, I W. (Jurnal Peternakan Tropika, 2021)
The research aims to find out the growth and yield of kaliandra plant ( Calliandra calothyrsus ) which is given various dosage of vermicompost fertilizer has been done in Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University on the highway Sesetan alley Markisa. The study Was conducted 10 weeks, using a complete randomized design (RAL) with five level of  treatments and six repeats so that there were 30 experimental units. The treatment given is a dosage of vermicompost fertilizer consisting of 0 tons/ha (D0), 5 tons/ha (D5), 10 tons/ha (D10), 15 tons/ha (D15), 20 tons/ha (D20). The observed variables are growth variables, yield variables and growth characteristic variables. The results showed that, the growth and yield of kaliandra plant ( Calliandra calothyrsus ) which was given various doses of vermicompost fertilizer differed significantly on the height of the plant, dry weight of leaves, dry weight of stems, dry weight of roots, dry weigh of total forage and leaf area of ??the pot. Based on the results of the study, it can be concluded that the application of vermicompost fertilizer is able to increase the growth and yield of kaliandra plants ( Calliandra calothyrsus ), and the dosage of vermicompost fertilizer 10 tons/ha produces the best growth and yield of kaliandra plants ( Calliandra calothyrsus ). Keywords: calliandra, dosage, growth, vermicompost, yield